In-situ growth of Zn–AgIn5S8 quantum dots on g-C3N4 towards 0D/2D heterostructured photocatalysts with enhanced hydrogen production. (14th June 2019) - Yang, Yalin; Mao, Baodong; Gong, Guan; Li, Di; Liu, Yanhong; Cao, Weijing; Xing, Lei; Zeng, Jun; Shi, Weidong; Yuan, Shouqi
Abstract: Photocatalytic water splitting for hydrogen production represents an ideal pathway for solar energy harvesting and conversion, for which narrow bandgap multinary sulfides play an important role. Here, series of Zn–AgIn5 S8 /g-C3N4 0D/2D nanocomposites were prepared by in-situ growth of the Zn–AgIn5 S8 quantum dots (QDs) on g-C3N4 nanosheets for improved charge separation. To our surprise, rather than a photoactive component, here g-C3N4 nanosheets act as a charge transfer mediator, where only a relatively low ratio is required. The as-fabricated Zn–AgIn5 S8 /g-C3N4 nanocomposites were systematically studied. When the mass ratio of g-C3N4 was 10%, the hydrogen production rate was maximized, which was 1.39 times higher than pure Zn–AgIn5 S8 QDs and 138.6 times higher than g-C3N4. The enhanced photocatalytic activity of the Zn–AgIn5 S8 /g-C3N4 nanocomposites is attributed to the intimate interface contact, which results in the effective separation and transfer of the photogenerated charge carriers as proved by the PL lifetime, transient photocurrent and electrochemical impedance spectra measurements. The Zn–AgIn5 S8 /g-C3N4 nanocomposites also exhibit excellent cycle stability. A plausible mechanism was proposed for the 0D/2D Zn–AgIn5 S8 /g-C3N4 composite photocatalysts. This work provides a relatively simple method for constructing high-quality 0D/2D heterostructure of QDs/nanosheets, as well as new insight for the efficiency improvement of narrow-bandgap sulfide photocatalysts. Graphical abstract: Image 1 Highlights: 0D/2D Zn–AgIn5 S8 /g-C3 N4 were prepared by a simple in-situ growth method. Zn–AgIn5 S8 /g-C3 N4 exhibited higher H2 production rate and longer carrier lifetime. The g-C3 N4 nanosheets act as the hole transfer mediator instead of light absorber.